Mechanisms and Effects of Macrophage Polarization and Its Specifics in Pulmonary Environment - Žaloudíková, M (Physiological research, 2023)
Macrophages are a specific group of cells found in all body tissues. They have specific characteristics in each of the tissues that correspond to the functional needs of the specific environment. These cells are involved in a wide range of processes, both pro-inflammatory and anti-inflammatory ("wound healing"). This is due to their specific capacity for so-called polarization, a phenotypic change that is, moreover, partially reversible compared to other differentiated cells of the human body. This promises a wide range of possibilities for its influence and thus therapeutic use. In this article, we therefore review the mechanisms that cause polarization, the basic classification of polarized macrophages, their characteristic markers and the effects that accompany these phenotypic changes. Since the study of pulmonary (and among them mainly alveolar) macrophages is currently the focus of scientific interest of many researchers and these macrophages are found in very specific environments, given mainly by the extremely high partial pressure of oxygen compared to other locations, which specifically affects their behavior, we will focus our review on this group.
Keywords: makrofágy; Macrophages; buněčná diferenciace; Cell Differentiation; Humans; Anti-Inflammatory Agents; antiflogistika; lidé